Nitrergic signalling via interstitial cells of Cajal regulates motor activity in murine colon - Lies, Barbara (J Physiol, 2015)
KEY POINTS: Dysregulation of nitric oxide (NO) signalling is associated with GI motility dysfunctions like chronic constipation, achalasia or Hirschsprung's disease. The inhibitory effect of NO is mainly exerted via NO‐sensitive guanylyl cyclase (NO‐GC) which is found in different gastrointestinal (GI) cell types including smooth muscle cells (SMCs) and interstitial cells of Cajal (ICC). Here, we focus on the investigation of NO‐GC function in murine colon. Using cell‐specific knock‐out mice, we demonstrate that NO‐GC is expressed in myenteric ICC of murine colon and participates in regulation of colonic spontaneous contractions in longitudinal smooth muscle. We report a novel finding that basal enteric NO release acts via myenteric ICC to influence the generation of spontaneous contractions whereas the effects of elevated endogenous NO are mediated by SMCS in the murine proximal colon. These results help in understanding possible pathological mechanisms involved in slowed colonic action and colonic inertia. ABSTRACT: In the enteric nervous systems, NO is released from nitrergic neurons as a major inhibitory neurotransmitter. NO acts via NO‐sensitive guanylyl cyclase (NO‐GC), which is found in different gastrointestinal (GI) cell types including smooth muscle cells (SMCs) and interstitial cells of Cajal (ICC). The precise mechanism of nitrergic signalling through these two cell types to regulate colonic spontaneous contractions is not fully understood yet. In the present study we investigated the impact of endogenous and exogenous NO on colonic contractile motor activity using mice lacking nitric oxide‐sensitive guanylyl cyclase (NO‐GC) globally and specifically in SMCs and ICC. Longitudinal smooth muscle of proximal colon from wild‐type (WT) and knockout (KO) mouse strains exhibited spontaneous contractile activity ex vivo. WT and smooth muscle‐specific guanylyl cyclase knockout (SMC‐GCKO) colon showed an arrhythmic contractile activity with varying amplitudes and frequencies. In contrast, colon from global and ICC‐specific guanylyl cyclase knockout (ICC‐GCKO) animals showed a regular contractile rhythm with constant duration and amplitude of the rhythmic contractions. Nerve blockade (tetrodotoxin) or specific blockade of NO signalling (l‐NAME, ODQ) did not significantly affect contractions of GCKO and ICC‐GCKO colon whereas the arrhythmic contractile patterns of WT and SMC‐GCKO colon were transformed into uniform motor patterns. In contrast, the response to electric field‐stimulated neuronal NO release was similar in SMC‐GCKO and global GCKO. In conclusion, our results indicate that basal enteric NO release acts via myenteric ICC to influence the generation of spontaneous contractions whereas the effects of elevated endogenous NO are mediated by SMCs in the murine proximal colon.